Incontinence affects health-related quality of life in children and adolescents with spina bifida. Issue 3 (June 2018) - Szymanski, Konrad M.; Cain, Mark P.; Whittam, Benjamin; Kaefer, Martin; Rink, Richard C.; Misseri, Rosalia
Summary: Purpose: Despite devoting many resources to managing urinary and fecal incontinence (UI and FI) in children with spina bifida (SB), it remains unclear whether either is associated with lower health-related quality of life (HRQOL). We sought to determine the impact of UI and FI on HRQOL in this population. Materials and methods: Children with SB (8–17 years) living in the United States were surveyed online and in SB clinics (2013–15). We evaluated incontinence over the previous 4 weeks using a UI dry interval (<4 h, ≥4 h), FI clean interval (<1 week, ≥ 1 week), and self-reported amount of UI and FI (for each: a lot, medium, a little, none). HRQOL was assessed with QUALAS, a validated SB-specific instrument. Linear regression was used. Results: The mean age of 298 children was 12.5 years (52.0% male). Overall, 73.1% had UI, 52.3% had FI, and 43.6% had both. Adjusting for concurrent UI and FI, any UI was associated with lower HRQOL in 14–17 year olds ( p  < 0.0001) and 10–13 year olds ( p  = 0.048), but not 8–9 year olds ( p  = 0.98) (Figure ). All age groups reported lower HRQOL with FI ( p  ≤ 0.0001). On multivariate analysis, UI and FI incontinence intervals were not associated with lower HRQOL for any age group ( p  ≥ 0.58 and p  ≥ 0.10, respectively). Higher quantities of UI were associated with ever-lower HRQOL, particularly in 14–17 year olds ( p  ≤ 0.02). Any quantity of FI was associated with lower HRQOL in all ages. The findings did not change significantly on exploratory analysis correcting for demographic and clinical variables. Discussion: We report the first evidence that incontinence matters to children and adolescents with SB. Being a cross-sectional study, we were unable to track HRQOL over time. A prospective study is required to assess if HRQOL impact of UI indeed changes as a child grows up and if improving incontinence with treatments improves HRQOL. Findings are similar to those reported in adults with SB and suggest that the concept of "social continence" based on time interval has no HRQOL relevance in children, adolescents or adults with SB. Conclusions: UI is negatively associated with HRQOL in children with SB in an age-dependent fashion: starting in 10 year olds and increasing until 14 years. FI correlates with lower HRQOL regardless of age. Similar to findings in adults with SB, HRQOL is lower with increasing amounts of UI and not the length of a dry interval. FI impacts HRQOL uniformly, regardless of frequency or amount. Figure Independent effects of urinary and fecal incontinence on health-related quality of life (HRQOL) in children, adolescents and adults with spina bifida. HRQOL was assessed by QUALAS Bowel and Bladder domain. Negative score differences signify lower HRQOL. Those without incontinence served as controls within each age group. Results for adults were obtained from 383 adults with spina bifid living in the United States enrolled in a separate, previously published international HRQOL study (Szymanski [13] ).